Corporate Social Responsibility and the Perception of Ethical Marketing among Students of Economics, Marketing, and Management - Yessentayeva, Aizhan; Nauryzbekova, Almara; Turakulova, Lavbarkhan; Kazanbayeva, Zhanar (BUKETOV BUSINESS REVIEW, 2026)
This study examines how university students understand and respond to the concept of Corporate Social Responsibility (CSR) and ethical marketing. The research involved 110 undergraduate students from economics, marketing, and management programs at South Kazakhstan University named after M. Auezov and was conducted using a quantitative, cross-sectional design. Data were collected online through Google Forms and WhatsApp to ensure accessibility and participation. The study tested three hypotheses: that higher CSR awareness is associated with more favorable attitudes toward socially responsible companies; that positive attitudes foster greater trust and socially responsible consumer behavior; and that students from different academic fields (Marketing, Management, and Economics) differ in their levels of CSR awareness and behavioral responses. The results show that students demonstrate a generally high level of CSR awareness (M = 4.96) and positive attitudes toward socially responsible companies (M = 4.87). Correlation analyses confirmed significant positive relationships between awareness, attitude, and behavioral impact, supporting the first two hypotheses. However, one-way ANOVA revealed no significant differences across fields of study, suggesting that CSR awareness and related behaviors are shared values among business students. Overall, the findings indicate that while CSR and ethical marketing are well recognized conceptually, practical understanding remains limited. The study recommends expanding CSR education through case-based and experiential learning and strengthening university–industry collaboration to cultivate ethical awareness and sustainable business values among future professionals.